Georgian naxiri (cattle) - Akkadian naxiru - Constantine B. Lerner, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
In the present article, an attempt is made to reveal a precise meaning of the word naxiru which, although referring to several animals, has not yet been defined. By analysing a number of arguments including the Georgian word naxiri (a herd) it is argued that this word in Assyrian sources denoted a sea cow.